Books
in black and white
Main menu
Share a book About us Home
Books
Biology Business Chemistry Computers Culture Economics Fiction Games Guide History Management Mathematical Medicine Mental Fitnes Physics Psychology Scince Sport Technics
Ads

Elementary Differential Equations and Boundary Value Problems - Boyce W.E.

Boyce W.E. Elementary Differential Equations and Boundary Value Problems - John Wiley & Sons, 2001. - 1310 p.
Download (direct link): elementarydifferentialequations2001.pdf
Previous << 1 .. 442 443 444 445 446 447 < 448 > 449 450 451 452 453 454 .. 609 >> Next

y" + p(x)y' + q(x)y = 0 we see that p(x) = 1/x and 22
q(x) = (x -1)/x . Thus x = 0 is a singular point and
2
since xp(x) 1 and x q(x) -1 as x 0, x = 0 is a
to
regular singular point. Substituting y = anxn+r into
n=0
22
x y" + xy' + (x -1)y = 0, shifting indices appropriately, and collecting coefficients of common powers of x we obtain [r(r-1) + r - 1]a0xr + [(1+r)r + 1 + r -1]a1xr+1
+ X {[(n+r)2 - 1]an + an-2}xn+r = 0.
n=2
2
The indicial equation is r -1 = 0 so the roots are r1 = 1
and r2 = -1. For either value of r it is necessary to
r+1
take a1 = 0 in order that the coefficient of x be zero.
The recurrence relation is [(n+r) - 1]an = -an-2,
n = 2,3,4... . For r = 1 we have an = -an-2/[n(n+2)],
n = 2,3,4,... . Since a1 = 0 it follows that a3 = a5 = a7
= ... = 0. Let n = 2m. Then a2m = -a2m-2/2 m(m+1), m =
oo
Section 5.7
93
22
1,2,..., so a2 = -a0/2 -1-2, a4 = -a2/2 -1-2-3 =
a0/22 22 1-2-2-3,..., and a2m = (-1)m a0/22nm!(m+1)!. Thus one solution (set a0 = 1/2) of the Bessel equation of
order one is J1(x) = (x/2) (-1) nx2n/(n + 1)!n!22n. The
n=0
ratio test shows that the series converges for all x.
Also note that J1(x) ^ 0 as x ^ 0.
16b. For r = -1 the recurrence relation is 2
[(n-1) - 1]an = -an-2, n = 2,3,... . Substituting n = 2
2
into the relation yields [(2-1) - 1]a2 = 0 a2 = -a0.
Hence it is impossible to determine a2 and consequently impossible to find a series solution of the form
x-1 X bnxR-
n=0
Secton 5.7, Page 278
1. The D.E. has the form P(x)y" + Q(x)y' + R(x)y = 0 with
P(x) = x, Q(x) = 2x, and R(x) = 6ex. From this we find p(x) = Q(x)/P(x) = 2 and q(x) = R(x)/P(x) = 6ex/x and thus x = 0 is a singular point. Since xp(x) = 2x and
2x
x q(x) = 6xe are analytic at x = 0 we conclude that x = 0 is a regular singular point. Next, we have
2
xp(x) ^ 0 = p0 and x q(x) ^ 0 = q0 as x ^ 0 and thus the
-2
indicial equation is r(r-1) + 0-r + 0 = r - r = 0, which has the roots r1 = 1 and r2 = 0.
3. The equation has the form P(x)y" + Q(x)y' + R(x)y = 0
2
with P(x) = x(x-1), Q(x) = 6x and R(x) = 3. Since P(x),
Q(x), and R(x) are polynomials with no common factors and
P(0) = 0 and P(1) = 0, we conclude that x = 0 and x = 1
are singular points. The first point, x = 0, can be shown
to be a regular singular point using steps similar to
those to shown in Problem 1. For x = 1, we must put the
D.E. in a form similar to Eq.(1) for this case. To do
this, divide the D.E. by x and multiply by (x-1) to
23 obtain (x-1) y + 6x(x-1)y + (x-1)y = 0. Comparing this
x
to Eq.(1) we find that (x-1)p(x) = 6x and (x-1) q(x) = 3(x-1)/x which are both analytic at
94
Section 5.7
x = 1 and hence x = 1 is a regular singular point. These last two expressions approach p0 = 6 and q0 = 0
respectively as x ^ 1, and thus the indicial equation is
r(r-1) + 6r + 0 = r(r+5) = 0.
-(1+x) 2
9. For this D.E., p(x) = ------- and q(x) = ---- and thus
x2(1-x) x(1-x)
x = 0, -1 are singular points. Since xp(x) is not
analytic at x = 0, x = 0 is not a regular singular point.
1+x 2 2(1-x)
Looking at (x-1)p(x) = ----- and (x-1) q(x) = - we
x2 x
see that x = 1 is a regular singular point and that
p0 = 2 and q0 = 0.
sinx cosx
17a. We have p(x) = -- and q(x) = -------, so that x = 0 is
22
xx
a singular point. Note that xp(x) = (sinx)/x ^ 1 = p0 2
as x ^ 0 and x q(x) = -cosx ^ -1 = q0 as x ^ 0. In order to assert that x = 0 is a regular singular point we
2
must demonstrate that xp(x) and xq(x), with xp(x) = 1 at 2
x = 0 and x q(x) = -1 at x = 0, have convergent power series (are analytic) about x = 0. We know that cosx is analytic so we need only consider (sinx)/x. Now
sinx = (-1) nx2n+1/(2n+1)! for -
n 2n+1
^ < x < so
n=0
(sinx)/x = (-1) nx2n/(2n+1)! and hence is analytic.
Previous << 1 .. 442 443 444 445 446 447 < 448 > 449 450 451 452 453 454 .. 609 >> Next